The Effect of Science, Technology, Engineering, and Mathematics (STEM) Approach on Science Literacy Skills of Grade IV Elementary School Students - Diani, Destina Inggrid; Nuraeni, Fitri; Hikmatunisa, Nenden Permas (Educational Studies and Research Journal, 2024)
Science literacy skills have a very important role in science learning because students are required to be able to solve problems by utilizing technology. The low level of science literacy in Indonesia is the basis for this research. The objectives of this study were: 1) Knowing the effect of the STEM approach on improving the science literacy of elementary school students; 2) Knowing and analyzing the improvement of science literacy skills of students who get learning with the STEM approach better than students who get learning with conventional approaches. The research method used in this research is Quasi Experimental Design with the form of Non-equivalent Control Group Design which involves two classes in its implementation and is given different treatments in learning science with the subject matter of Changes in the Form of Objects with a subject of 43 students. The instrument used to obtain data before and after learning is a science literacy test instrument. Based on the research conducted, the conclusions were obtained; 1) There is an effect of STEM approach on science literacy skills of fourth grade students. 2) There is an increase in science literacy skills of students who get learning with the STEM approach better than students who get learning with conventional approaches.